The perimenopause, depressive disorders, and hormonal variability - Soares, Cláudio de Novaes; Cohen, Lee Stuart (São Paulo Medical Journal, 2001)
CONTEXT: Several investigations have postulated that the perimenopause may represent a period of increased psychiatric vulnerability, particularly for mood disorders. This review characterizes the perimenopause, including biological changes, the influence of psychosocial factors and the most common clinical manifestations. Clinic-based studies and community-based surveys addressing the prevalence of depressive symptoms in perimenopausal women are critically reviewed. We also discuss the potential greater vulnerability to mood disturbance during the perimenopause in response to hormonal variability. A therapeutic algorithm for management of depressive symptoms in middle-aged perimenopausal women is also presented. The role of estrogen in the treatment of perimenopausal depressive symptoms is particularly discussed. In addition, we review the existing data regarding the potential efficacy of estrogen as an antidepressant agent (monotherapy, augmentation strategy or prophylaxis). DESIGN: Narrative review.